The GIST of it all: management of gastrointestinal stromal tumors (GIST) from the first steps to tailored therapy : a bibliometric analysis - Musa, Julian; Kochendörfer, Sarah; Willis, Franziska; Sauerteig, Christine; Harnoß, Jonathan M.; Rompen, Ingmar F.; Grünewald, Thomas G. P.; Saeedi, Mohammed al; Schneider, Martin; Harnoß, Julian-Camill (Langenbeck's archives of surgery, 2024)
Purpose: Improvement of patient care is associated with increasing publication numbers in biomedical research. However, such increasing numbers of publications make it challenging for physicians and scientists to screen and process the literature of their respective fields. In this study, we present a comprehensive bibliometric analysis of the evolution of gastrointestinal stromal tumor (GIST) research, analyzing the current state of the field and identifying key open questions going beyond the recent advantages for future studies to assess. Methods: Using the Web of Science Core Collection, 5040 GIST-associated publications in the years 1984–2022 were identified and analyzed regarding key bibliometric variables using the Bibliometrix R package and VOSviewer software. Results: GIST-associated publication numbers substantially increased over time, accentuated from year 2000 onwards, and being characterized by multinational collaborations. The main topic clusters comprise surgical management, tyrosine kinase inhibitor (TKI) development/treatment, diagnostic workup, and molecular pathophysiology. Within all main topic clusters, a significant progress is reflected by the literature over the years. This progress ranges from conventional open surgical techniques over minimally invasive, including robotic and endoscopic, resection techniques to increasing identification of specific functional genetic aberrations sensitizing for newly developed TKIs being extensively investigated in clinical studies and implemented in GIST treatment guidelines. However, especially in locally advanced, recurrent, and metastatic disease stages, surgery-related questions and certain specific questions concerning (further-line) TKI treatment resistance were infrequently addressed. Conclusion: Increasing GIST-related publication numbers reflect a continuous progress in the major topic clusters of the GIST research field. Especially in advanced disease stages, questions related to the interplay between surgical approaches and TKI treatment sensitivity should be addressed in future studies.